PENGARUH MODEL KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) DENGAN MEDIA ULAR TANGGA FISIKA TERHADAP MINAT, MOTIVASI DAN HASIL BELAJAR SISWA SMPN 10 KOTA BENGKULU - Titin Sundari; Andik Purwanto; Eko Risdianto (Kumparan Fisika, 2017)
This study aimed to examine the effect of cooperative learning model TGT using physics ladder snake media to enthusiasm, motivation and student learning outcomes. The method used is a quasi experimental design with nonequivalent control group design  conducted in class VIII SMPN 10 Cities 2016/2017 academic year. The sampling technique usedmethod.  perposive sampling  Collecting data using a questionnaire to students' interest and motivation to the application of the model and test for learning outcomes. Based on the analysis of data obtained an average  N-sciencegain process skillsof 0.49 to 0.35 for the experimental class and control class. The average  N-gain interest in learning of 0.61 to 0.36 for the experimental class and control class. The average  N-gain motivation to learn of 0.67 to 0.48 for the experimental class and control class. The average  N-gain learning outcomes of 0.74 to 0.62 for the experimental class and control class. As for the two independent samples t-test is thitung greater than ttabel  that of 4.14> 2.01 for the interest in learning, 3.95> 2.01 for students' motivation and 3.28> 2.01 for student learning outcomes at significant level ( ? = 0.05). So we can conclude: there is the effect of the application of cooperative learning model TGT using physics ladder snake media to enthusiasm, motivation and learning outcomes of students of SMPN 10 Bengkulu City.Keywords: Cooperative Team Games Tournament (TGT), snake ladder media, learning interest, learning motivation.